Adiponectin/AdipoR1 Axis Promotes IL-10 Release by Human Regulatory T Cells - Ramos-Ramírez, Patricia; Malmhäll, Carina; Tliba, Omar; Rådinger, Madeleine; Bossios, Apostolos (Frontiers in Immunology, 2021)
Background: Adiponectin is an important immunomodulatory mediator in inflammatory conditions. While we previously showed that adiponectin receptor 1 (AdipoR1) is expressed in murine regulatory T cells (Tregs), its expression in human Tregs remain unknown. Here, we examined the expression of AdipoR1 in human Tregs and whether its ligand, globular adiponectin (gAd) affects the Treg ability to secrete IL-10 and the role of Type 2 (T2) inflammation in such process. Methods: Human Tregs from peripheral blood were analyzed by flow cytometry for AdipoR1, Helios and IL-10 expression. CD4+ T cells enriched from peripheral blood mononuclear cells (PBMCs) were cultured in the presence or the absence of gAd or the chemical adiponectin receptor agonist, AdipoRon, or in a T2 cytokine milieu. Flow cytometry was then used to assess intracellular IL-10, IL-10 secreting cells, FOXP3 and Helios expression, and phosphorylated p38 MAP kinase (MAPK). IL-10 levels in CD4 T cell supernatants were quantified by ELISA. Results: We found that a subset of human Tregs expressed AdipoR1. Importantly, more Heliosˉ cells expressed AdipoR1 than Helios+ cells. Likewise, there was a higher frequency of IL-10+ cells within Heliosˉ AdipoR1+ Tregs compared to Helios+ AdipoR1+ Tregs. In contrast, the IL-10 mean fluorescence intensity (MFI) was higher in Helios+ AdipoR1+ Tregs compared to HeliosˉAdipoR1+ Tregs. When human CD4+ T cells were treated with gAd or AdipoRon, a significant increase in IL-10 secretion, FOXP3 expression, and p38 MAPK phosphorylation was observed in Heliosˉ AdipoR1+ Tregs. Interestingly, gAd under T2 cytokine milieu significantly increased the intracellular levels of IL-10, mainly in Helios+ AdipoR1+ Tregs, and IL-10 levels in supernatants of CD4+ T cells. Conclusions: Collectively, our findings suggest that adiponectin/AdipoR1 axis promotes IL-10 release by Tregs, mainly in Heliosˉ Tregs, and the effect was amplified by T2 inflammation in Helios+ Tregs.